Theoretical-Experimental Approach of Chitosan/Quaternized Chitosan Nanofibers' Behavior in Wound Exudate Media - Bianca-Iustina Andreica; Alexandru Anisiei; Manuela-Maria Iftime; Razvan-Vasile Ababei; Lacramioara Ochiuz; Decebal Vasincu; Ingrid-Andrada Vasilache; Constantin Volovat; Diana Boboc; Vladimir Poroch; Lucian Eva; Maricel Agop; et al. (MDPI AG, 2023)
This study aimed to investigate the behavior of chitosan/quaternized chitosan fibers in media mimicking wound exudates to understand their capacities as wound dressing. Fiber analysis of the fibers using dynamic vapor sorption proved their ability to adsorb moisture up to 60% and then to desorb it as a function of humidity, indicating their outstanding breathability. Dissolution analyses showed that quaternized chitosan leached from the fibers in water and PBS, whereas only small portions of chitosan were solubilized in water. In media containing lysozyme, the fibers degraded with a rate determined by their composition and pH, reaching a mass loss of up to 47% in media of physiologic pH. Notably, in media mimicking the wound exudate during healing, they adsorbed moisture even when their mass loss due to biodegradation was high, whereas they were completely degraded in the media of normal tissues, indicating bioabsorbable dressing capacities. A mathematical model was constructed, which characterized the degradation rate and morphology changes of chitosan/quaternized chitosan fibers through analyses of dynamics in scale space, using the Theory of Scale Relativity. The model was validated using experimental data, making it possible to generalize it to the degradation of other biopolymeric systems that address wound healing.